1999
DOI: 10.1046/j.1365-2621.1999.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genetic variants of α‐lactalbumin and β‐lactoglobulin from milk of native Portuguese ovine and caprine breeds

Abstract: Summary α‐Lactalbumin (α‐La) and β‐lactoglobulin (β‐Lg) fractions were obtained from Portuguese native breeds of ewes and goats by preparative gel filtration and further purified by ion exchange; their genetic variants were characterized by isolectric focusing, and β‐Lg isolated was further characterized by differential scanning calorimetry. Separation of β‐Lg and α‐La by molecular exclusion from native whey was relatively easy, whereas β‐Lg from both breeds accounted for a single peak via ion exchange under v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
(20 reference statements)
4
8
0
1
Order By: Relevance
“…This phenomenon can be attributed to the main role of hydrophobic interactions in the stability of proteins and particularly of tyrosyl residues of b-lactoglobulin A in such interactions. Pintado and Malcata [10] have found a good correlation between the pI of whey proteins and the temperature of denaturation (78-97 8C) for pH values in the range 3.5-7.0, in the presence of NaCl. Therefore, ovine b-lactoglobulin B shows a higher temperature of denaturation than ovine b-lactoglobulin A.…”
Section: Calorimetry Measurementsmentioning
confidence: 92%
See 3 more Smart Citations
“…This phenomenon can be attributed to the main role of hydrophobic interactions in the stability of proteins and particularly of tyrosyl residues of b-lactoglobulin A in such interactions. Pintado and Malcata [10] have found a good correlation between the pI of whey proteins and the temperature of denaturation (78-97 8C) for pH values in the range 3.5-7.0, in the presence of NaCl. Therefore, ovine b-lactoglobulin B shows a higher temperature of denaturation than ovine b-lactoglobulin A.…”
Section: Calorimetry Measurementsmentioning
confidence: 92%
“…It was also found that heat capacity at pH 2 is lower than at neutral pH for the whole b-lactoglobulin since the unfolded state (prevailing at neutral pH) has a higher heat capacity than the compact denatured state observed at acid pH [31]. The difference observed between the two variants in their temperature of denaturation is dependent on the conditions used in the experiments (pH and ionic strength), which affect the thermal transition of the two b-lactoglobulin variants [10]. This difference in Td at pH 2 shows that b-lactoglobulin A is more heat resistant than the variant B, what agrees with the results of Calavia and Burgos [26] working at a different pH (6.6) but is in disagreement with those reported in the case of the bovine counterpart [32].…”
Section: Calorimetry Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of caprine whey protein polymorphism and its impact on the properties of caprine milk are even more limited (Pintado & Malcata, 1996;Recio, Pe´rez-Rodrı´-guez, Ramos, & Amigo, 1997;Moioli et al, 1998;Pintado & Malcata, 1999), in contrast to numerous studies that have been carried out on caprine casein polymorphism and its influence on the compositional and technological characteristics of caprine milk. Nucleotide sequence of caprine b-LG cDNA and deduced amino acid sequence of caprine b-LG have been presented by Folch, Coll, and Sa´nchez (1993).…”
Section: Introductionmentioning
confidence: 99%